Revisiting the Labial Pit Organ Pathway in the Noctuid Moth, Helicoverpa armigera - KC, Pramod; Chu, Xi; Kvello, Pål; Zhao, Xin-Cheng; Wang, Gui-Rong; Berg, Bente Gunnveig (Frontiers in Physiology, 2020)
Lepidopteran species detect CO2 via a specialized organ located on the peripheral segment of the labial palps, the labial palp pit organ (LPO). Based on tracing of LPO sensory neurons targeting one distinct antennal-lobe glomerulus, Kent and her colleagues described the projections originating from the LPO in the sphinx moth as ‘an accessory olfactory pathway in Lepidoptera’ already in the 1980ties. In spite of similar reports from studies of other lepidopteran species, however, it has been an unresolved issue whether additional termination areas of the labial pit nerve, such as the gnathal ganglion and the ventral nerve cord, are actually output sites of LPO neurons. Since the previous studies have interpreted slightly differently about the projection pattern occurring from the classical mass staining, we performed selective mass staining from the inside of the pit and from the outer surface of the peripheral palp. The results demonstrated that the LPO sensory neurons project exclusively to LPO glomerulus (LPOG), whereas the non-LPO sensory neurons target the gnathal ganglion and the ventral nerve cord. Additional iontophoretic staining of individual LPO sensory neurons, performed from the LPO and the LPOG, showed three morphological neuron types: one bilateral targeting the LPOG in both antennal lobes, one unilateral targeting the ipsilateral LPOG only, and one contralateral targeting the LPOG in the other antennal lobe. Finally, to explore putative differences in the projection pattern of neurons housed by two previously reported sensillum types in the pit, i.e. hair-shaped sensilla located distally and club-shaped sensilla located proximally, we performed mass staining from different levels of the peripheral palp. We found that the sensory neurons originating from the two sensillum types display slightly different projection patterns.